2000
DOI: 10.1080/00016470052943928
|View full text |Cite
|
Sign up to set email alerts
|

Function after Achilles tendon rupture in the elderly: 25 patients older than 65 years followed for 3 years

Abstract: We retrospectively analyzed the function after Achilles tendon rupture in 25 patients older than 65 years, 3 (1-5) years after the initial treatment. The patients' median age at the time of injury was 71 (65-86) years. The initial management was surgical in 14 patients and non-surgical (8-week immobilization) in 10, 1 patient was not treated.The ratio of the number of heel-raises on the injured to the uninjured side was median 0.64 (0-1.14), showing a reduction in performance. However, in both surgically-and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…In our study, we had two of 27 patients (7%) with a new episode of rupture. Our results were comparable in terms of complications to the study of Nestorson et al [46]. One patient of that study had a deep venous thrombosis, and four had superficial infections requiring antibiotics.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In our study, we had two of 27 patients (7%) with a new episode of rupture. Our results were comparable in terms of complications to the study of Nestorson et al [46]. One patient of that study had a deep venous thrombosis, and four had superficial infections requiring antibiotics.…”
Section: Discussionsupporting
confidence: 87%
“…The authors concluded that AT rupture in patients older than 65 years reduces lower limb function, and that complications are common following surgical management. No ATRS data were presented in that study [46].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations